The Path to Nirvana: Exploring Buddhist Concepts in Kim - Bhatta, Arjun Dev (The Batuk, 2025)
This research paper investigates the Buddhist concepts of ‘nirvana’ in Kipling’s Kim mainly through the lens of the central character Teshoo Lama. In Buddhism, ‘nirvana’ is a key term that refers to achieving mental peace and a supreme state of bliss by extinguishing the flames of tempting desires, attachment, and ignorance. I have mainly focused on some of the authentic texts and opinions of the Western and Eastern Buddhist scholars for the theoretical aspects of this article, and it claims that Kipling makes the Buddhist notions of ‘nirvana’ explicit through the portrayal of the Tibetan Buddhist Teshoo Lama, who seeks mental peace by ending his desires through enlightenment. He strives to detach himself from earthly desires to achieve a deeper understanding of life and ultimately reaches to the state of ‘nirvana’. This article also explores how Kim’s secular journey for identity and material gratification is influenced by his companionship with the Lama and his gradual immersion in the Lama’s teachings, transforming his quest into a pursuit of higher enlightenment and mental peace. Furthermore, this article concludes that humankind’s attachment to ephemeral objects is a source of suffering, and inner peace can be achieved through knowledge, wisdom, and ethical conduct, rather than becoming entangled in illusory materialistic pursuits such as love, affection, ego, and greed.